On the criteria of distinction between labour contract and contract of service - Вишновецька, Світлана Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In the article an author analyzes the criteria of distinction between labour contract and contract of service which are important to determine the legal nature of relations between the parties. In particular, the author researches a criterion of on-going or one-time nature of the relations between the parties involved, which is often used in legal literature to distinguish labour and civil legal relations. Also the author notes that under the labour contract the employee makes some type of work within the limits of specific work functions in the general production process specified in the labour contract. Under the contract of service the executer makes a concrete task. Achieving the specific results, execution of a concrete task within the limits of particular work function is not the ground for termination of labour relations. As a rule, labour relations tend to continue after the execution of a task, since the employee has certain work functions. So, every new task in labour relations should not be determined by a special contract. The criterion of subordination also recognized by the ILO is thoroughly researched. Based on the analysis the author concludes that the employee, under the control and supervision of the employer, executes certain work functions determined by the labour contract. Therefore, it is the criterion of supervision (control). At the same time, nowadays it is often takes place when the employer has no objective possibility to control the work process because of its territorial indefiniteness and nature of the employee’s work function. It means that the work on the territory or facility is not under a direct or indirect control of the employer. Therefore, this criterion is not effective by itself. The author substantiates the suitability of using a complex of criteria for effective regulation of labour relations. So, the labour contract describes the execution of labour function in the interests, under the control and supervision of the employer with the employee’s integration in the organizational structure of the company.